‘Coming out’/self-disclosure in LGBTQ+ adolescents and youth: International and Indian scenario - A narrative review of published studies in the last decade (2012-2022) - Swapnajeet Sahoo; Velprashanth Venkatesan; Rahul Chakravarty (Indian Journal of Psychiatry)
Background: People who identify themselves as Lesbian, Gay, Bisexual, Transgender, Queer, and others (LGBTQ+) go through a process of self-exploration and self-identification during adolescence, and the process resolves when one decides to self-disclosure. The experience of ‘Coming Out’ (CO) can be positive, leading to acceptance and a feeling of liberation, or it can be harmful, leading to stigma, humiliation, and discrimination, subsequently leading to significant psychological distress. Aim: This study was to do a narrative review on the studies published in the area/topic of CO in youth in the last decade (2012-2022) and to look for factors that act as barriers and facilitators of CO. Additionally, we have tried to look for differences in CO in LGBTQ+ adolescents and youth in the Western world vis-a-vis Indian/Eastern societies. Materials and Methods: An extensive literature search in electronic databases, PUBMED, Web of Science, EMBASE, Medline, Scopus, and search engine ‘Google Scholar’ using specific search terms and assessment of all published articles until 20th May 2023 was done. Results: Twenty-three studies were found eligible for data extraction, which discussed the problems faced during the CO process. Most of the studies are from developed countries, and only one is from India. Eleven were qualitative studies, 11 were cross-sectional studies, and one was a case study. The qualitative studies focused on generating themes of CO along with various issues/problems faced by the participants. The cross-sectional studies mainly explored parental reactions, stigma, parental support, psychological distress, and perceived stress in the participants. Major themes emerging from the qualitative studies were the experience of prejudice from various strata of society, such as parental, societal, racial, cultural, and religious factors that lead to problems of hiding, internalized homophobia, and anticipatory rejections that put this population under extreme conditions. Limited research is available from Eastern societies. More recently, the new generation of adolescents has taken the help of social media platforms for self-disclosure. Conclusions: CO is an elaborate multi-step process that considers the presence of parental/family and societal support, cultural/traditional values, and several psychosocial factors that determine the degree of positive outcomes. Emerging data indicated an improved trend of adolescents deciding to come out to families or in online platforms, both of which are associated with challenges, more in eastern collectivistic societies and developing countries.